Revision and phylogenetic analysis of the Papuan weevil genus Thyestetha Pascoe (Coleoptera, Curculionidae, Cryptorhynchinae) - Eberle, Jonas; Tänzler, Rene; Riedel, Alexander (Zootaxa, 2012)
Thyestetha Pascoe, an apterous genus of Papuan Cryptorhynchinae is revised. It contains two previously describedspecies, T. carbonaria Faust and T. nitida Pascoe, plus seven new species: T. discolor sp. n., T. emarginata sp. n.,T. glabra sp. n., T. lubrica sp. n., T. oblita sp. n., T. puncticollis sp. n., and T. splendens sp. n.. Lectotypes are designatedfor T. carbonaria, T. nitida, and Pantoxistus rubripennis Chevrolat which is a junior synonym of T. nitida (syn. n.). Thegenus and its species are described and the characters relevant for their identification are illustrated. A key to the speciesis provided. Phylogenetic analyses are performed, utilizing molecular and morphological approaches. A maximumlikelihood tree including 5 Thyestetha species and 2 outgroups is presented, based on 3 mitochondrial and 4 nuclearmarkers. A maximum parsimony analysis of 19 morphological characters includes all described species. Thyestetha ispresumably closely related to Telaugia Pascoe and Elichora Pascoe. The group is restricted to New Guinea and some smaller neighboring islands.